Genetics of Inflammatory Bowel Disease: Current Understanding and Future Directions - P. K. Chandra Sekar; R. Veerabathiran (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to present literature data on the genetic underpinnings of inflammatory bowel disease (IBD), focusing on key genetic variants such as NOD2, ATG16L1, and IL23R; The objective of this was to understand how these genetic factors contribute to immune dysregulation, epithelial barrier dysfunction, and mucosal homeostasis in IBD.Key points. IBD, encompassing Crohn's disease and ulcerative colitis, is intricately shaped by a nexus of genetic and environmental factors, and its global prevalence is increasing. Genetic research has identified pivotal variants — NOD2, ATG16L1, and IL23R — linked to IBD, influencing key pathways, such as autophagy, interleukin signaling, and bacterial management. These genetic variants, integral to IBD's etiology of IBD, have functional significance because they perturb immune regulation, compromise epithelial barrier integrity, and disrupt mucosal homeostasis, collectively contributing to intestinal inflammation through diverse mechanisms. Early detection of IBD is paramount for arresting disease progression and underscoring the importance of prognostic testing and genetic screening, especially in cases with familial predispositions or very early onset IBD. Additionally, the use of certain IBD medications, such as corticosteroids, azathioprine, and infliximab, may have implications for male fertility, necessitating a nuanced understanding of these potential effects for informed decision-making in IBD management. This comprehensive understanding of the genetic landscape, functional implications, and diagnostic strategies is vital for advancing personalized treatments and improving outcomes in individuals with IBD.Conclusion. IBD is a complex gastrointestinal disorder influenced by a combination of genetic and environmental factors. Genetic variants, including NOD2, ATG16L1, and IL23R, contribute to dysregulation of immune responses, epithelial barrier function, and mucosal homeostasis. While progress has been made in understanding the genetic landscape of IBD, ongoing research is needed to elucidate the functional consequences of these variants, identify causal genes, and explore gene-environment interactions. This deeper understanding holds the potential for more precise diagnostics and personalized treatments, ultimately improving outcomes in individuals living with IBD.